In vitro morphogenic response from different explants of sweet basils, Ocimum basillicum L. - Siti Zubaidah Lood (Tanjong Malim, 2018)
In vitro morphogenic response from different explants of sweet basils, Ocimum basillicum L. by Siti Zubaidah Lood